Responding to climate change in Asian cities governance for a more resilient urban future - Archer, Diane 1984-; Colenbrander, Sarah; Dodman, David (Abingdon, Oxon Routledge, 2017)
"The role of cities in addressing climate change is increasingly recognized in international arenas, including the Sustainable Development Goals, the UN Framework Convention on Climate Change, and the New Urban Agenda. Asia is home to many of the countries that are most vulnerable to climate change impacts and, along with Africa, will be the site of most urban population growth over the coming decades.Bringing together a range of city experiences, Responding to Climate Change in Asian Cities provides valuable insights into how cities can overcome some of the barriers to building climate resilience, including addressing the needs of vulnerable populations. The chapters are centred on an overarching understanding that adaptive urban governance is necessary for climate resilience. This requires engaging with different actors to take into account their experiences, vulnerabilities and priorities; building knowledge, including collecting and using appropriate evidence; and understanding the institutions shaping interactions between actors, from the national to the local level"--Provided by publisher.
Keywords: City planning -- Environmental aspects -- Asia; City planning -- Climatic factors -- Asia; Climatic changes -- Asia; Urban ecology (Sociology) -- Asia